Um esquema de coopera??o codificada com c?digos produto turbo de paridade simples para canais com desvanecimento r?pido - Barbosa, Guilherme Varela (2014)
In this dissertation it is proposed a new coded cooperation scheme based on single parity-check turbo-product codes, in which the channel softinformation from the source and the relays are combined in a novel way at the destination: differently from conventional approaches in which the diversity bits are in the parities, here the diversity bits are placed in the message part of the codeword. Besides having simple encoding and decoding, the proposed scheme unveils potential for large cooperation gains in fast fading channels. As a case study, its performance is assessed by computer simulation under the action of a blind decision algorithm for cooperation. Attractive performance gains are achieved, depending on the conditions of the channel between the source node and the relays, and between the relay nodes and the destination.